2020
DOI: 10.1590/1983-40632020v5064026
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity in integrated crop-livestock systems increases the soil enzymatic activity in the short term

Abstract: Integrated crop-livestock systems (ICLS) intercropped in the pasture phase promote alterations in the dynamics of soil attributes, among them the enzymatic activity. This study aimed to evaluate soil enzymatic and microbial activities, following the implementation of ICLS with increased plant diversity during the pasture phase. The study consisted of soybean cultivation at season and pasture with different diversity levels in the off-season: very low - monocropped Urochloa brizantha cv. BRS Paiaguás with no an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…As observed in the CT samples (Figure 5), enzyme activity can be an efficient bioindicator of soil changes, particularly SOM formation and degradation processes or nutrient mineralization [7,44,74,77]. This finding is consistent with previous studies in the Brazilian Cerrado that have shown that enzyme activity is sensitive to land use and management practices [44,72,[78][79][80].…”
Section: Relationships Among Management Grain Yield and Soil Temperat...supporting
confidence: 89%
“…As observed in the CT samples (Figure 5), enzyme activity can be an efficient bioindicator of soil changes, particularly SOM formation and degradation processes or nutrient mineralization [7,44,74,77]. This finding is consistent with previous studies in the Brazilian Cerrado that have shown that enzyme activity is sensitive to land use and management practices [44,72,[78][79][80].…”
Section: Relationships Among Management Grain Yield and Soil Temperat...supporting
confidence: 89%